Like snow we fall - Dade, Ayla, 1994- (Dade, Ayla, 1994- Winter Dreams., 2025)
"Paisley Harris has done her best to overcome her troubled past: growing up in a trailer park in Minneapolis with her drug-addicted mother and being exploited by her figure skating coach. So when she's given a way out by applying for iSkate, a prestigious skating school in Aspen, Colorado, she takes it, seeking a fresh start in the picturesque winter landscape. Knox Winterbottom, a celebrated and arrogant snowboarder, stands on the precipice of a new level in his career. Known for his rebellious and carefree nature, he battles his own demons. When Paisley and Knox meet, their worlds collide: she, the disciplined and determined athlete, and he, the unpredictable and charismatic risk-taking sportsman. Despite his numerous romantic entanglements, he has a strict rule against dating figure skaters. Yet slowly, their attraction pulls them together. Paisley gets a job at the Winterbottoms' chalet, desperately in need of the money and lodgings. But with Paisley and Knox under the same roof, it's only a matter of time before they can't keep their hands off each other"--Amazon website.